HUBUNGAN UMUR DAN STATUS GIZI DENGAN KADAR GULA DARAH PENDERITA DIABETES MELITUS TIPE II - eny - masruroh (Akademi Keperawatan Dharma Husada Kediri, 2018)
Diabetes Mellitus (DM) type II is the most common type. Type II DM can increase significantly as people's lifestyle changes and increased age over 40 years and obesity problems are characterized by an increase in body mass index (BMI) ≥ 25 Kg / m2. Excessive BMM can cause blood sugar levels to increase because the body becomes resistant to insulin. This study to determine the relationship between age and nutritional status based on BMI with blood sugar levels in patients with type II DM in Poly Diseases In RSUD dr. Iskak Tulungagung. The data were collected on 19-20 April 2017. The research design used correlational analytic. Population of all DM type II patients in Poly Disease In RSUD dr. Iskak Tulungagung using Quota Sampling technique with 30 respondents. Taking IMT variable data using scales and microtoa scales. While the variable blood sugar levels using glucotest stick. Then the data were analyzed by paired t test.The results of this study on average BMI 25.77 Kg / m2 with an average blood sugar levels 213,23 mg / dL. From the statistical test results show there is a relationship between age with blood sugar levels indicated p value = 0.00.begitu also on the test of nutritional status with blood sugar levels in patients with type II DM in the Poly Diseases In RSUD dr. Tulungagung Iskak shown with p value = 0,000 and α 0.05 which means p <0.05 which means there is a correlation between the two. Based on the research, there is a relationship between age and nutritional status with blood sugar levels it is recommended for respondents with excess BMI can maintain ideal body weight and in patients with type II DM at age more than 40 years more maintain a healthy lifestyle that can prevent complications diabetes due to high blood sugar levels.